Heavy Metals (Hg and As) Concentration in Mining Endowed Enclaves in Ghana (American Journal of Energy and Natural Resources, 2023)
Levels of heavy metals in mining areas differ from region to region depending on the level of operations and activities engaged at the mining site. The study assessed the extent of heavy metals contamination in the available water and sediments in mining endowed enclaves in Ghana. A total of forty-eight (48) samples, 24 each of water and sediments samples were taken. At each mining site, 4 samples each of water and sediments samples were taken and studied. Water and sediment samples were taken to the laboratory to determine level of mercury and arsenic. For the sediments, the average levels of Hg ranged from 0.057-0.145ppm and that of As levels in the soil sediments ranged from 0.084-0.087ppm. The average levels of Hg in water samples ranged from 0.010-0.086ppm and that of As levels in the water samples ranged from 0.004-0.008ppm. There were significance differences (p